"There are Two People at Work that I'm Fairly Certain are Black": Uncertainty and Deliberative Thinking in Blind Race Attribution. Issue 3 (3rd February 2016) - Friedman, Asia
Abstract : Geneticists, biologists, social scientists, and humanist scholars have powerfully critiqued race as a stable set of biological categories. Despite this, in everyday life, race is consistently assumed to be visually available in physical features. Racial categories also continue to be used in scientific and social scientific research as if they were self‐evident and real. In this study, I examine the role of visual perception in the construction of racial categories and their recalcitrance in everyday thought and interaction. My observations are based on in‐depth interviews with 25 blind people, which highlight the unique features of their nonvisual, non‐appearance‐based experiences of race.